PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN APLIKASI ADOBE DREAMWEAVER CS6 DENGAN METODE INKUIRI PADA MATERI GARIS SINGGUNG PERSEKUTUAN DUA LINGKARAN - Mohammad Salman (Delta: Jurnal Ilmiah Pendidikan Matematika, 2018)
The rapid progress of science and technology in the world of education underlies the existence of learning by utilizing Information Technology as a learning medium, one of which is known by the term web-based learning. The development of instructional media using Adobe Dreamweaver CS6 application with inquiry method in the tangents of circle alliance aims to overcome the problems in the learning process in SMP Muhammadiyah Pekajangan which still use simple learning media. This development research uses the Borg & Gall development model. The stages are research and data collection, product design, product validation, product trial and product improvement. The purpose of this study is to develop a quality learning media by testing the validity and validity of the learning media. Based on the result of the research, the average of total aspect from all validator 4.7. While the calculation of the value of practicality of learning media from questionnaire response obtained percentage of 85.19%. According to the criteria of validity and the criteria of practicality it can be concluded that the learning media developed valid and practical.